Taxation for African economic development - Taylor, Milton C.; University of Ife. (London : Published for the Institute of Administration, University of Ife, Nigeria by Hutchinson Educational, 1970)
While the principal emphasis is given to domestic revenue resources, Part 1 is deliberately broad in order that the role of taxation may be viewed in the broader context of fiscal policy in an African setting.
Includes bibliographical references: p. [535]-540.
osc 10/12/2018
Loans
Keywords: Taxation; Fiscal policy